Compute W(y1,y2) where y1 and y2 are solutions of the differential equation y"+y'+y=0
y''+y'+y=0 is a linear homogeneous differential equation with constant coefficients.
The solution is sought in the form of an exponent y = "e^{\\lambda x}" .
We write the characteristic equation assuming that
y' = "\\lambda""e^{\\lambda x}" ; y'' = "\\lambda"2"e^{\\lambda x}"
Hence
"\\lambda"2"e^{\\lambda x}" + "\\lambda""e^{\\lambda x}" + "e^{\\lambda x}" = 0 or "e^{\\lambda x}" ( "\\lambda"2 + "\\lambda" + 1) = 0
"\\lambda"2 + "\\lambda" + 1 = 0 is the caracteristic equation.
The above equation is the standard quadratic equation:
D = b2 - 4ac; a=b=c=1
D = 12 -4*1*1 = -3
"\\lambda"1,2 = "\\frac{ - b \u00b1 \\sqrt{\\smash[b]{D}}}{2a}"
"\\lambda"1 = "\\frac{ - 1 + i \\sqrt{\\smash[b]{3}}}{2}"
"\\lambda"2 = "\\frac{ - 1 - i \\sqrt{\\smash[b]{3}}}{2}"
y = c1exp( "\\lambda"1x) + c2exp( "\\lambda"2x)
y1 = c1exp( "\\frac{ - 1 + i \\sqrt{\\smash[b]{3}}}{2}"x)
y2 = c2exp( "\\frac{ - 1 - i \\sqrt{\\smash[b]{3}}}{2}"x)
If y = u(x)+iv(x) is a solution to the equation then y1=u(x) and y2=iv(x) (here i = "\\sqrt-1" ) are solutions too.
Hence:
we can write
y1=c1"e^\\frac{-x}{2}"sin("\\frac{\\sqrt3}{2}"x);
y2=c2"e^\\frac{-x}{2}" cos("\\frac{\\sqrt3}{2}"x)
W = "\\begin{vmatrix}\n y_1 & y_2 \\\\\n y'_1 & y'_2\n\\end{vmatrix}"
y'1 = c1"\\lbrace" -"\\frac{1}{2}""e^\\frac{-x}{2}"sin("\\frac{\\sqrt{\\smash[b]{3}}}{2}"x) +"\\frac{\\sqrt{\\smash[b]{3}}}{2}""e^\\frac{-x}{2}"cos("\\frac{\\sqrt{\\smash[b]{3}}}{2}"x)"\\rbrace"
y'2 = c2"\\lbrace" -"\\frac{1}{2}""e^\\frac{-x}{2}"cos("\\frac{\\sqrt{\\smash[b]{3}}}{2}"x) -"\\frac{\\sqrt{\\smash[b]{3}}}{2}""e^\\frac{-x}{2}"sin("\\frac{\\sqrt{\\smash[b]{3}}}{2}"x)"\\rbrace"
W = "\\begin{vmatrix}\n c_1e^\\frac{-x}{2}sin(\\frac{\\sqrt3}{2}x) & c_2e^\\frac{-x}{2}cos(\\frac{\\sqrt3}{2}x) \\\\\n \\frac{c_1e^\\frac{-x}{2}}{2}\\lbrace-sin(\\frac{\\sqrt3}{2}x)+\\sqrt3cos(\\frac{\\sqrt3}{2}x)\\rbrace & \\frac{-c_2e^\\frac{-x}{2}}{2}\\lbrace cos(\\frac{\\sqrt3}{2}x)+\\sqrt3sin(\\frac{\\sqrt3}{2}x)\\rbrace\n\\end{vmatrix}" =
= "c_1e^\\frac{-x}{2}sin(\\frac{\\sqrt3}{2}x)(\\frac{-c_2e^\\frac{-x}{2}}{2})\\lbrace cos(\\frac{\\sqrt3}{2}x)+\\sqrt3sin(\\frac{\\sqrt3}{2}x)\\rbrace-"
"- c_2e^\\frac{-x}{2}cos(\\frac{\\sqrt3}{2}x)(\\frac{c_1e^\\frac{-x}{2}}{2})\\lbrace-sin(\\frac{\\sqrt3}{2}x)+\\sqrt3cos(\\frac{\\sqrt3}{2}x)\\rbrace ="
"= - \\frac{c_1c_2}{2}e^{-x}\\lbrace \\bcancel{cos(\\frac{\\sqrt3}{2}x)sin(\\frac{\\sqrt3}{2}x)} - \\bcancel{cos(\\frac{\\sqrt3}{2}x)sin(\\frac{\\sqrt3}{2}x)} +\n \\\\ +\\sqrt3sin^2(\\frac{\\sqrt3}{2}x)+\\sqrt3cos^2(\\frac{\\sqrt3}{2}x) \\rbrace="
"=- \\frac{\\sqrt3}{2}c_1c_2e^{-x}"
"if\\\\ c_1=c_2=1 \\\\W = =- \\frac{\\sqrt3}{2}e^{-x}"
Comments
Leave a comment